Tobacco smoking and semen quality in infertile males: a systematic review and meta-analysis - Bundhun, Pravesh Kumar (BMC Public Health, 2019)
BACKGROUND: Nowadays, the total number of couples visiting an infertility clinic is on the rise. Tobacco smoking is considered one of the major factors leading to male infertility. In this study, we aimed to systematically investigate the impact of tobacco smoking on semen quality in infertile male participants. METHODS: Online databases (Cochrane Central database of Randomized Controlled Trials and the databases of MEDLINE and EMBASE respectively) were searched for relevant English publications that satisfied the inclusion and exclusion criteria of this analysis. The clinical endpoints which were assessed included semen parameters (oligozoospermia, asthenozoospermia, teratozoospermia, and azoospermia), morphological defects of spermatozoa and the hormones involved in reproduction. RevMan 5.3 software was used to analyze the data whereby mean difference (MD) and risk ratios (RR) with 95% confidence intervals (CI) were generated to represent the results. RESULTS: Sixteen studies with a total number of 10,823 infertile male participants (5257 smokers and 5566 non-smokers) were included. Results of this analysis showed oligozoospermia to be significantly higher in smokers (RR: 1.29, 95% CI: 1.05–1.59; P = 0.02). Morphological defect of spermatozoa (MD: 2.44, 95% CI: 0.99–3.89; P = 0.001) was also significantly higher in smokers whereby significant head (MD: 1.76, 95% CI: 0.32–3.20; P = 0.02), neck (MD: 1.97, 95% CI: 0.75–3.18; P = 0.002) and tail (MD: 1.29, 95% CI: 0.35–2.22; P = 0.007) defects were observed. However, smoking did not affected the pH (MD: 0.04, 95% CI: [− 0.03–0.11]; P = 0.30) and motility (RR: 1.42, 95% CI: 0.97–2.09; P = 0.07) of spermatozoa. Additionally, tobacco smoking did not cause any dis-balance in hormones which were involved in reproduction. CONCLUSIONS: In conclusion, with reference to the clinical endpoints which were studied in this analysis, tobacco smoking was associated with a lower sperm count and an increase in the number of morphological defects of spermatozoa. However, the pH and motility of spermatozoa as well as the production of hormones which were involved in reproduction were not affected in this population of infertile males.